Next generation natural killer cells for cancer immunotherapy: the promise of genetic engineering. (April 2018) - Daher, May; Rezvani, Katayoun
Highlights: NK cells play a critical role in cancer immune surveillance. NK cellular therapy is safe but has some limitations. Genetic engineering strategies are being employed to overcome these limitations. Abstract : Recent advances in the field of cellular therapy have focused on autologous T cells engineered to express a chimeric antigen receptor (CAR) against tumor antigens. Remarkable responses have been observed in patients receiving autologous CD19-redirected T cells for the treatment of B-lymphoid malignancies. However, the generation of autologous products for each patient is logistically challenging and expensive. Extensive research efforts are ongoing to generate an off-the-shelf cellular product for the treatment of cancer patients. Natural killer (NK) cells are attractive contenders since they have potent anti-tumor activity, and their safety in the allogeneic setting expands the cell sources for NK cell therapy beyond an autologous one. In this review, we discuss advantages and limitations of NK cellular therapy, and novel genetic engineering strategies that may be applied to overcome some of the limitations. Next-generation engineered NK cells are showing great promise in the preclinical setting and it is likely that in the next few years CAR-engineered NK cells will be incorporated into the current armamentarium of cell-based cancer therapeutics.